2011
DOI: 10.1021/jp2073649
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics of Isolated Fluorenone

Abstract: The ultrafast dynamics of isolated 9-fluorenone was studied by femtosecond time-resolved photoionization and photoelectron spectroscopy. The molecule was excited around 264-266 nm into the S(6) state. The experimental results indicate that the excitation is followed by a multistep deactivation. A time constant of 50 fs or less corresponds to a fast redistribution of energy within the initially excited manifold of states, i.e., a motion away from the Franck-Condon region. Internal conversion to the S(1) state t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Its rate is faster by 10 3 times as compared to similar aromatic ketones, such as fluorenone with a slow ISC to T 1 . 18 Since the characterization of the intersystem crossing mechanism is crucial for the photochemistry of benzophenone, we have revisited here the time evolution in the gas phase of cooled benzophenone after excitation to the second singlet S 2 at 266 nm. At the same time, we have investigated also benzophenone deposited on argon clusters under the same experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Its rate is faster by 10 3 times as compared to similar aromatic ketones, such as fluorenone with a slow ISC to T 1 . 18 Since the characterization of the intersystem crossing mechanism is crucial for the photochemistry of benzophenone, we have revisited here the time evolution in the gas phase of cooled benzophenone after excitation to the second singlet S 2 at 266 nm. At the same time, we have investigated also benzophenone deposited on argon clusters under the same experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Photoionization and photoelectron spectroscopy studies suggested fluorenone is excited up to 264-266 ns by multi deactivation steps (50 fs interval) to S 6 state. [22] The oligomer of fluorenones acts as a donor during excitation and emission suggesting covalent diphenylacetylene bond useful for intramolecular energy transfer between porphyrin units. [23] In supramolecular chemistry and materials science, shape-persistent arylene ethynylene macrocycles play an important role due to their novel properties and potential applications.…”
Section: Importance Of Fluorenones In Materials Sciencesmentioning
confidence: 99%
“…This review covers all the reported synthetic protocols to access fluorenones by intermolecular, intramolecular, and oxidative approaches. substituted carboxylic acid fluorenone (20), (ii) acylation of [1,1'-biphenyl]-2-carboxylic acid (21), and (iii) hydrolysis of 19 to biphenyl dicarboxylic acid anhydride (22), which may undergo decarboxylation. However, the yield was low.…”
Section: Importance Of Fluorenones In Materials Sciencesmentioning
confidence: 99%
“…25,26 However, although multiphoton absorption 27,28 in uorenone derivatives has been reported many times, systematic investigations into excited-state associated nonlinear absorption are rare. [29][30][31] Furthermore, most of the research focuses on nonlinear absorption (NLA), little attention has been paid to the ultrafast nonlinear refraction (NLR) in uorenone derivatives.…”
Section: Introductionmentioning
confidence: 99%